Photodynamic inactivation of antibiotic-resistant bacteria in whole blood using riboflavin photodynamic method - Zhu, Liguo; Li, Changqing; Wang, Deqing (Frontiers in Microbiology, 2024)
Treating bacteremia caused by antibiotic-resistant bacteria is a global concern. Antibacterial photodynamic inactivation is a promising strategy to combat it. However, it’s challenging to achieve the inactivation of antibiotic-resistant bacteria in whole blood because of its opacity and complexity. We investigated a riboflavin photodynamic method to effectively inactivate antibiotic-resistant bacteria in whole blood. Four strains of antibiotic-resistant bacteria were isolated, identified, and cultured in this research: methicillin-resistant Staphylococcus aureus (MRSA), pan-drug-resistant Acinetobacter baumannii (PDRAB), ESBLs-producing Escherichia coli (EPEC) and pan-drug-resistant Klebsiella pneumoniae (PDRKP). To simulate bacteremia, antibiotic-resistant bacteria was added into whole blood. Whole blood was treated using riboflavin photodynamic method with ultraviolet irradiation (308 nm and 365 nm ). The ultraviolet irradiation dose was divided into 18J/cm2, 36J/cm2, and 54J/cm2. Microbial count of antibiotic-resistant bacteria in whole blood was used for evaluating inactivation effectiveness. The roles of red blood cells, lymphocytes, coagulation factors, and platelets in whole blood were assessed. In results, inactivation effectiveness increased as the ultraviolet dose increased from 18 J/cm2 to 54 J/cm2. At the dose of 18 J/cm2, inactivation effectiveness of four antibiotic-resistant bacteria were more than 80 %, while only 67 % of MRSA. The antibacterial effect was enhanced by the combination of riboflavin photodynamic treatment and antibiotic. The red blood cell function was susceptible to ultraviolet dose. At the dose of 18 J/cm2, hemolysis rate was less than 0.8 % and there was no change in levels of ATP and 2,3-DPG. At the same dose, the proliferation, cell killing, and cytokine secretion activities of lymphocytes decreased 20 - 70 %; Factor Ⅴ and Factor VIII activities decreased 50 %; Fibrinogen and platelet function loss significantly but reparable. Consequently, we speculated that riboflavin photodynamic method with a ultraviolet dose of 18 J/cm2 was effective in inactivating four antibiotic-resistant bacteria in whole blood while whole blood function was preserved. We also provided a novel extracorporeal circulation phototherapy mode for treating bacteremia caused by antibiotic-resistant bacteria.